Awareness About Non-Communicable Diseases among Rural Population in Remote Villages of Nepal (Indian Journal of Public Health Research & Development, 2020)
Non-communicable diseases constitute a significant part of the overall morbidity and mortality in Nepal.Prevention of non-communicable diseases involves lifestyle modification which is directly dependent onthe awareness of the population of the risk factors for diseases and methods of prevention. The aim of thisstudy was to estimate the levels of awareness about three common non-communicable diseases among theresidents of remote villages in Nepal. The study was conducted in villages in 5 districts of Nepal using a directinterview method after obtaining verbal consent of the participants. The study included 218 participants,of whom 127 were female and 91 were male. The participants ranged in age from 18-93 years. Levels ofawareness about causative factors of hypertension, asthma and diabetes among the respondents were 62.2%,22.5% and 50.9% respectively. Levels of awareness of preventive methods among the participants were52.8%, 38.9% and 55.3% for hypertension, asthma and diabetes respectively. The difference in levels ofawareness among both genders, different age groups and differing educational status was also studied.
Keywords: awareness; hypertension, asthma, diabetes, non-communicable diseases, rural Nepal